Mental Health Status of Inmates in Indonesia - Nia Aulia; Asnawi Abdullah; Basri Aramico; Marthoenis Marthoenis; Nurjanah Nurjanah (Indonesian Journal of Global Health Research, 2024)
Mental health disorders are conditions of a person who experiences disorders related toclinical,cognitive function, emotional regulation, and behavior. The purpose of this study was to explore in depth the mental health of assisted citizens in class III Lhoknga prison, Aceh Besar Regency. This study used qualitative research design with a phenomenological descriptive approach. Data collection with semi-structured interviews. The informants in this study amounted to nine informants of assisted citizens in one of the prisons in Aceh. Data analysis using Michael Huberman's model starts from data collection, data reduction, data presentation, conclusion drawing and verification. The results of the study found four research themes, including feelings about mental health while in prison with sub-themes of fostered citizens' opinions on mental health, and mental health conditions while serving sentences. Personal conditions that are haunted by guilt with the sub-theme of self-acceptance, events that result in fostered residents feeling trauma and feelings that can affect the mental health of fostered residents. It is expected that the prison will provide services and education related to mental health that can be utilized by assisted residents and can be carried out sustainably to fostered residents. The mental health condition of the inmates when viewed from the BPS aspect, namely biological, psychological, social, all inmates experience problems both from a biological, psychological and social perspective. The trigger for this happened was because there were no mental health services in prison.